1997
DOI: 10.1080/0042098976087
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants from the Former Soviet Union in the Israeli Housing Market: Spatial Aspects of Supply and Demand

Abstract: In the 1950s and 1960s the Israeli government did not let market forces absorb the immigrants, disperse them spatially and find them jobs. 'Planning from above' dominated immigrant absorption. The absorption of the immigrants from the former Soviet Union in the past five years is marked by a completely new policy conception, known in Israel as 'direct absorption'. The Israeli government decided to replace its strategy of intervention from above with a strategy of absorption by market forces. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 7 publications
2
28
0
Order By: Relevance
“…There is some empirical evidence that the availability of housing may be a moving force behind longer-distance migration as well. Thus, in his studies of spatial distribution of foreign immigrants and internal migrants in Israel, Lipshitz (1997Lipshitz ( , 1998 concluded that some migrants chose to settle in the country's peripheral regions despite a shortage of employment there, because government-subsidised housing resulted in fairly low housing prices in these districts.…”
Section: Housing Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…There is some empirical evidence that the availability of housing may be a moving force behind longer-distance migration as well. Thus, in his studies of spatial distribution of foreign immigrants and internal migrants in Israel, Lipshitz (1997Lipshitz ( , 1998 concluded that some migrants chose to settle in the country's peripheral regions despite a shortage of employment there, because government-subsidised housing resulted in fairly low housing prices in these districts.…”
Section: Housing Factorsmentioning
confidence: 97%
“…Availability of housing is often seen as a key factor affecting migration, particularly where it occurs over relatively short distances and does not result in a change of place of work (Clark and van Lierop, 1986;Stambùl and Sùrensen, 1989;Burnley et al, 1997;Portnov and Pearlmutter, 1997;Lipshitz, 1997Lipshitz, , 1998Green et al, 1999).…”
Section: Housing Factorsmentioning
confidence: 98%
“…Israel is an immigrant society and since the establishment of the Jewish state in 1948 the government has been involved in the housing market, initiating new building and providing subsidized mortgages (Lipshitz, 1997). Housing policy is viewed as the means for rapid absorption of immigrants and for enhancing their commitment to the country.…”
Section: The Israeli Contextmentioning
confidence: 99%
“…In the first year the government adopted a strategy of immigrant absorption by market forces (Lipshitz, 1997). On arrival, immigrants were provided with a certain amount of money that partly covered their expenses for rental housing.…”
Section: The Israeli Contextmentioning
confidence: 99%
“…On landing in Israel, immigrants now receive an absorption basket from Revue de l'integration et de la migration internationale 165 the government, with a certain sum of money meant to last for a limited time. Immigrants are now expected to find housing and jobs during their first months in the country through informal networks (Lipshitz, 1996).…”
Section: The Israeli Contextmentioning
confidence: 99%